2005
DOI: 10.1007/s00234-005-1412-6
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of the cervical disc: histology compared with radiography and magnetic resonance imaging

Abstract: Decisions about the treatment of neck pain are largely made on the basis of information gained from plain X-rays and magnetic resonance imaging (MRI), which are used routinely as part of preliminary investigation. We performed a descriptive cadaveric study to compare histology with radiography and MRI. We correlated plain radiography, disc height [Farfan index (FI)] and MRI findings with histology to assess the ability of radiology to detect significant pathologic lesions. The study included 52 motion segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Previous reports disclosed a lack of correlation between MRI/MCs scale and HDS [36,37]. Possible explanations for this finding are as follows: (1) sampling discrepancy, expected to be obvious in cases involving the lumbar spine because the protruded portion, rather than the whole disc, is removed; (2) use of qualitative and less complex grading criteria to obtain MRI/MCs scale [22]; (3) dehydration of the IVD detected on MRI (based on T2-weighted protocols) may simply represent the aging process rather than pathological IVD degeneration [38,39]; (4) fissures and cell clusters within the IVD seen under a microscope may not be detected with current MRI methodologies [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports disclosed a lack of correlation between MRI/MCs scale and HDS [36,37]. Possible explanations for this finding are as follows: (1) sampling discrepancy, expected to be obvious in cases involving the lumbar spine because the protruded portion, rather than the whole disc, is removed; (2) use of qualitative and less complex grading criteria to obtain MRI/MCs scale [22]; (3) dehydration of the IVD detected on MRI (based on T2-weighted protocols) may simply represent the aging process rather than pathological IVD degeneration [38,39]; (4) fissures and cell clusters within the IVD seen under a microscope may not be detected with current MRI methodologies [24].…”
Section: Discussionmentioning
confidence: 99%
“…The broad scope of MMP function expands their potential role as activators or inhibitors of tissue remodeling, with effects in the context of cardiovascular disease and obesity [15]. Currently, 24 MMPs have been recognized in humans. These are categorized into six groups: collagenases, gelatinases, stromelysins, matrilysins, membrane-type MMPs, and other types [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cervical disc degeneration is frequently found on MRI, even in the absence of neck pain. Christe et al5) reported that disc herniation (above of bulging) was found in 30.6% of asymptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile spondylolisthesis was defined as a greater than 3% difference in slip percentage when comparing standing lateral radiographs with MRIs, as has been previously reported [10]. Disc height was assessed by anterior and posterior heights and the Farfan index was calculated by dividing the sum of the anterior and posterior heights by the disc width [9,18]. Facet effusion was determined by measuring the effusion width orthogonal to the facet joint [4,10].…”
Section: Imaging Assessmentmentioning
confidence: 99%